Overeducation: New evidence for 25 European countries - Christina Boll; Julian Sebastian Leppin; Anja Rossen; André Wolf (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
This study investigates the incidence of overeducation among workers in the EU and its underlying factors based on the most recent wave of the European Labor Force Survey (EU-LFS 2013). Its main purpose is to shed light on the interplay of so far neglected explanatory factors such as household characteristics and field of study as well as to reveal country differences in the impact of these factors. Therefore, our innovative features are the large number of determinants as well as the considerable amount of European countries simultaneously analyzed. Moreover, we differentiate in our analysis between high- and medium-skilled workers. Our findings point to a considerable variation in the potential determinants of overeducation across countries as well as across skill levels. This variation is not restricted to jobrelated characteristics, but interestingly also concerns household variables. Among those determinants showing a largely uniform influence are nationality, job tenure, temporary employment and presence of unemployed household members. – – Basierend auf der jüngsten Welle der Europäischen Arbeitskräfteerhebung (EU-LFS 2013) untersuchen wir in dieser Studie das Ausmaß und die Determinanten von formaler Überqualifikation unter Beschäftigten in EU-Staaten. Hierbei werden bislang vernachlässigte Erklärungsfaktoren wie zum Beispiel das Studienfach oder der Haushaltskontext berücksichtigt. Darüber hinaus differenzieren wir in unserer Analyse zwischen Personen mittlerer und hoher Bildung. Unsere Ergebnisse deuten auf eine beträchtliche Variation der Effekte zwischen einzelnen Ländern sowie zwischen den Qualifikationsniveaus hin. Diese Variation findet sich nicht nur bei den arbeitsplatzbezogenen Charakteristika, sondern auch bei den Haushaltsvariablen. Zu denjenigen Variablen, die einen weitgehend einheitlichen Einfluss auf das Risiko, überqualifiziert zu sein, haben, gehören Nationalität, Betriebszugehörigkeitsdauer, befristete Beschäftigung und die Anwesenheit von arbeitslosen Haushaltsmitgliedern.
Keywords: J24; J21; J22; 330; Overeducation; Realized Matches; European Labour Force; Economics of the Household